Un manejo rotacional para reducir la tasa de endogamia en un núcleo de ovinos Manchegos - Herrera, Victor Gaspar; Maizon, Daniel Omar; Alvarez Ocampo, Sonia Viviana; Gonzalez, Maria Florencia (Asociación Argentina de Producción Animal (AAPA), 2025)
Ponencia y poster